2021
DOI: 10.3390/ijerph18052491
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Dental Service Use Based on the Andersen Model: A Systematic Review

Abstract: Background: A systematic review synthesizing studies examining the determinants of dental service use drawing on the (extended) Andersen model is lacking. Hence, our purpose was to fill this knowledge gap; Methods: Three established electronic databases (PubMed, PsycInfo, as well as CINAHL) were searched. Observational studies focusing on the determinants of dental service use drawing on the Andersen model were included; Results: In sum, 41 studies have been included (ten studies investigating children/adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 74 publications
(297 reference statements)
1
42
0
1
Order By: Relevance
“…As the previous literature has shown, oral health status is the major determinant in the use of dental services [10,19]. Reporting good dental health was positively associated with initial utilization and negatively related to ensuing total expenditure.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…As the previous literature has shown, oral health status is the major determinant in the use of dental services [10,19]. Reporting good dental health was positively associated with initial utilization and negatively related to ensuing total expenditure.…”
Section: Discussionmentioning
confidence: 73%
“…The total sample comprised 6222 individuals. The choice of explicative variables was based on determinants from the last systematic review [10].…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…A Brazilian study did not find a significant association between use of dental service in previous 3 years and depressive symptoms [ 6 ]. Interestingly, a systematic 2021 review reported that the components of Andersen’s behavioural model are more likely to be associated with DSU in children, whereas predisposing, enabling, and need-based factors have not been consistently associated with DSU in adults [ 12 ]. In adults, a link between increased dental service use and higher education (predisposing factor) was found [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature identified five personality characteristics that are associated with use of preventive health care use [13]: conscientious (individuals tend to be careful and/or diligent and are usually task and goaldirected), neuroticism (individuals tend to feel depressed, anxious, impulsive, and display angry hostility), openness to experience (individuals being imaginative and are open for new ideas), extraversion (individuals are sociable and outgoing), and lastly agreeableness (individuals are compliant, tend to be altruistic and warm). Yet, the association between personality factors and use of dental services remains largely unexplored [14][15][16].…”
Section: Introductionmentioning
confidence: 99%